Connecting patients with clinical trials using patient navigation: a scoping review protocol - Caroline Hamm; Megan Delisle; Nicole Askin; Olla Hilal; Pratham Gupta; Nasong Anthony Luginaah; Leena Moshref; Carla Epp; Renee Nassar; Roaa Hirmiz; Milica Paunic; Mahmoud Hossami; et al. (BMJ Open)
Introduction Interventions are needed to increase participation in clinical trials through optimised trial design and enrolment workflows. Patient navigation is a promising intervention for increasing participation in clinical trials by optimising enrolment workflows. Patient navigation is defined as a personalised intervention aimed at overcoming barriers and ensuring timely access to healthcare services, diagnosis, treatment and care. This scoping review aims to fill a gap in current literature by summarising what is known about patient navigation, aiming to increase clinical trial participation.Methods and analysis A search was conducted for peer‐reviewed literature published in English from inception through 21 December 2023, and the search was updated on 5 March 2025. Sources of literature included Cochrane CENTRAL (Ovid), MEDLINE (Ovid), EMBASE (Ovid), Cumulative Index of Nursing and Allied Health (CINAHL; on EBSCOhost; EBSCO Industries, Inc), Epistemonikos and PROSPERO databases. Searches were also conducted through the Turning Research into Practice and International Clinical Trials Registry Platform (WHO) databases, Google Scholar and the Agency for Health Research and Quality platform to ensure the retrieval of all relevant articles. Reference lists of eligible studies were also examined. The Google Scholar search was limited to the first 10 pages of results. The search strategy focused on the following key concepts: navigation (eg, navigator, care coordination, case management) and clinical trials. Searches were reviewed using the PRESS Peer Review of Electronic Search Strategies 2015. This review was guided based on the JBI methodology for scoping reviews using a five-step review process: identify the research questions; search and identify relevant studies; select studies based on a priori criterion; chart the data; and collate, summarise and report the results according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews.Ethics and dissemination This scoping review identifies and analyses existing research; therefore, ethics approval is not required. Findings will be disseminated through conference presentations and a publication in a scientific journal.